Remapping Portuguese contemporary cinema with feminine territories - Pereira, Ana Sofia (2021)
Book review of the recently released Women's Cinema in Contemporary Portugal (by Mariana Liz and Hilary Owen), which aims to remap Portuguese cinema in the last fifty years to include feminine territories and thus granting visibility to women filmmakers and their work.